Ensino de artrópodes utilizando realidade aumentada - SILVA, Fabiano Reis da (Universidade Federal do Pará, 2021)
This paper describes a validation study of an educational product configured in an Augmented Reality application, hereby denominated “AR3D”, which combines three-dimensional virtual images of 60 (sixty) specimens of animals belonging to the Arthropoda phylum, together with the real world. This application may be used as a pedagogical resource, assisting science and/or biology teachers and students alike. The methodology chosen for this work involved two stages: the first stage consisted in building and structuring the AR3D application inside an integrated development environment (IDE) known as Unity 3D, with the intent of giving the application compatibility with camera-equipped mobile devices which run the Android operating system. The second stage consisted in the validation proper; said validation was conducted by a panel of experts, composed by five teacher trainers from the Federal University of Pará (UFPA), who belong to a post-graduate studies program dedicated to the training of science and biology teachers, as well as training in specific biology branches. An online form was made available to those teachers, as a means of data collecting. After all empirical data was gathered, an analysis was made, based on the following criteria: technical, user reaction and manual. The positives evidenced inside those criteria were: performance efficiency, reliability, safety, manual, motivation, user experience and knowledge. The sole criterium to receive a negative evaluation was usability: this was due to a low score concerning the adaptability of the tool to handicapped people. As the application’s positives outweigh the negatives, it is concluded that said application can be a tool with pedagogical potential to contribute with science and biology teaching, specifically in what concerns to studies involving arthropods.